A survey of antiepileptic drug responses identifies drugs with potential efficacy for seizure control in Wolf–Hirschhorn syndrome - Twede, Hope (Epilepsy & Behavior, 2018)
Seizures are present in over 90% of infants and children with Wolf-Hirschhorn syndrome (WHS). When present, they significantly affect quality of life. The goal of this study was to use caregiver reports to describe the comparative efficacies of commonly used antiepileptic medications in a large population of individuals with WHS. A web-based, confidential caregiver survey was developed to capture seizure semiology and a chronologic record of seizure treatments as well as responses to each treatment. Adverse events for each drug were also cataloged. We received 141 complete survey responses (47% response rate) describing the seizures of individuals ranging in age from 4months to 61years (90 females: 51 males). Using the Early Childhood Epilepsy Severity Scale (E-Chess), WHS-associated seizures are demonstrably severe regardless of deletion size. The best-performing antiepileptic drugs (AEDs) for controlling seizures in this cohort were broad spectrum drugs clobazam, levetiracetam, and lamotrigine; whereas, the three commonly used carboxamide class drugs: carbamazepine, phenytoin, and oxcarbazepine, were reported to have little effect on, or even exacerbate, seizures. The carboxamide class drugs, along with phenobarbital and topiramate, were also associated with the highest rate of intolerance due to cooccurrence of adverse events. Levetiracetam, clobazam, and clonazepam demonstrated higher tolerability and comparatively less severe adverse events (Wilcoxon rank sum comparison between performance of levetiracetam and carboxamide class drugs gives a p<0.0001 after multiple comparison adjustment). This is the largest survey to date assessing WHS seizures. This study design is susceptible to possible bias, as the data are largely drawn from caregiver report and investigators had limited access to medical records. Despite this, our data suggest that the genetic etiology of seizures, together with an accurate electroclinical delineation, are important components of drug selection, even in contiguous gene syndromes which may have complex seizure etiologies.